Association of mental health and nutritional knowledge with drug abuse risk among islamic boarding school adolescents - Abdul Gani; Sri Andala; Liza Wahyuni; Agusri Agusri (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Drug abuse remains a significant public health concern among adolescents, including those attending Islamic boarding schools. Mental health and nutritional knowledge are important factors related to risky behaviors. This study aimed to examine the mental health status and nutritional knowledge in relation to drug abuse risk among adolescents. A cross-sectional study was conducted among 152 students at the Ihyauussunnah Islamic Boarding School in Lhokseumawe, Indonesia, selected using simple random sampling. Data were collected using a structured questionnaire assessing mental health, nutritional knowledge, and drug abuse risk. Descriptive statistics and chi-square tests with odds ratios were performed. Most participants had good nutritional knowledge (80.3%) and mental health status (86.8%), whereas 84.2% were categorized as having a low risk for drug abuse. Poor nutritional knowledge was associated with a higher risk of drug abuse (odds ratio [OR] =1.88; p=0.021), and poor mental health was associated with an increased risk (OR=1.72; p=0.042). Male students had a higher risk compared to female students (P =0.032). In conclusion, mental health status and nutritional knowledge were significantly associated with drug abuse risk among adolescents. These findings highlight the importance of integrated health education and mental health support programs in Islamic boarding schools.